EMPLOYING GENRE BASED APPROACH WITH AUDIO DIALOGUE TO ENHANCE STUDENTS’ SPEAKING PERFORMANCE - Rahmi Rahmi; Asnawi Muslem; Bukhari Daud (Universitas Syiah Kuala, 2020)
This study was aimed at investigating whether the implementation of Genre-Based Approach through Audio Dialogue can significantly enhance students’ speaking performance of SMPN 2 Muara Tiga and finding out the students’ responses toward the implementation of Genre Based Approach with Audio Dialogue. To achieve the purposes, the present study employed a quasi experimental research design. The population of the study is 100 students. By employing random sampling technique, 40 students were selected to be the sample of the study, comprising 20 students in class VIII-1 as an experimental class, and 20 students in class VIII-3 as a control class. To collect the data, the instruments employed were a series of tests, namely, pre-test and post-test, and also questionnaire. The data obtained from pre-test and post-test were analysed by employing SPSS 23 to find out t-test value of two classes, namely, experimental and control class. In addition, the data obtained from the questionnaire’s result were also analysed by employing SPSS 23 to examine the students’ responses of experimental class toward the use of Genre Based Approach with Audio Dialogue. The result of t-test showed that ttest (4.269) is higher than ttable (2.086). Employing independent samples t test, the sig. 2-tailed value (0,007) (0.05) revealed that Ha is accepted and H0 is rejected. Additionally, the students gave a very positive responses (90%) toward the use of Genre Based Approach with Audio Dialogue. To sum up, the implementation of Genre based Approach with audio dialogue is effective in enhancing students’ speaking performance in terms of accuracy, comprehensibility, and fluency and motivation. It is recommended that future related research conduct a study with integrated skills.